Performance of mortars with the Performance of mortars with the addition of septic tank sludge ash of septic tank sludge ash - Ingunza, Maria Del Pilar Durante (2018)
This paper studies the performance of mortars with the addition of septic tank sludge ash (SA). The sludge is a non-dangerous and non-inert residue. The cement-sand content is 1:3, in mass, commonly used for masonry in building construction. The percentages of sludge ash additions were 5, 10, 15, 20, 25 and 30% related to the cement mass. The results show that the addition of SA improves the general condition of the mortars, within the limits studied in this paper, providing better performance on both fresh and hardened states 2017